STRATEGI PENANAMAN NASIONALISME PADA PONDOK PESANTREN (Studi Kasus Tentang Penanaman Nasionalisme pada Santri Pondok Pesantren Sunan Gunungjati Ba’alawy, Gunungpati, Semarang) - Asrori Arafat; Rosyid Ridlo (Journal of Development and Social Change, 2019)
Nationalism is a form of expression of the love of citizens in the country's homeland. Today many young generations start to fade the soul of its nationalism so researchers want to know how the institution of boarding schools implanted nationalism to the students. This research took location in Sunan Gunungjati Ba’alawy Boarding School, Gunungpati, Semarang. The theory used in this study was the action theory put forward by Max Weber. This type of research is case studies, data is taken with in-depth interview techniques, observations, and documentation. Researcher use purposive sampling techniques and to ensure the validity of the used data triangulation source. From the results of the study can be concluded that the strategi of Sunan Gunung Jati Ba’alawy Boarding School in instilling nationalism is done with daily activities conducted by students, such as when living in the hut, to do something inside the hut. Through the activities of the week and every month, such as Roan, grave pilgrimage, study, Khitobah, and so forth. And also annual activities, such as activities on Islamic holidays, the Prophet's mawlid days, to the agenda activities of the country. Some factors that support among them are the concern of the surrounding community, teachers who can always be an example, the enthusiasm of students, and also good relations with the TNI and Police. But there are some things that become barriers, such as natural condition, students who had less sensitive to the surrounding. The implementation of this research will be expected to be a good example of other formal and non-formal education in cultivating nationalism to the younger generation.